The Existence of Muslim Women in the End Times: The Perspective of QS Al-Ahzab Verses 32 and 33 in the Tafsir Al-Mishbah - Siti Rohmah; Mohammad Fattah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article aims to analyze the existence of Muslim women in the end times through the interpretation of QS Al-Ahzab verses 32 and 33 in Tafsir Al-Mishbah by M. Quraish Shihab. This study uses a qualitative approach with a type of library research. Primary data was obtained from Tafsir Al-Mishbah, while secondary data came from various literature relevant to the study of interpretation and Muslim women. The results show that the existence of Muslim women in the end times from the perspective of the Qur'an is reflected through morality, communication ethics, maintaining personal honor, and the ability to maintain Islamic identity amidst the challenges of modernity. QS Al-Ahzab verses 32 and 33 emphasize the importance of maintaining modesty, ethics in speaking, and the prohibition of tabarruj (displaying excessive charm) as a form of moral protection for Muslim women. Thus, the values in these verses remain relevant as ethical guidelines for Muslim women in facing the development of the times without losing their Islamic identity.